Phenology and Dwarfing Gene Interaction Effects on the Adaptation of Selected Wheat (Triticum aestivum L.) Advanced Lines across Diverse Water-Limited Environments of Western Australia - Dowla, M; Islam, S; Stefanova, Katia; O'Hara, G; Ma, W; Edwards, I (Versita, 2020)
Photoperiod, vernalization, and plant height controlling genes are major developmental genes in wheat that govern environmental adaptation and hence, knowledge on the interaction effects among different alleles of these genes is crucial in breeding cultivars for target environments. The interaction effects among these genes were studied in nineteen Australian advanced lines from diverse germplasm pools and four commercial checks. Diagnostic markers for the Vrn-A1 locus revealed the presence of the spring allele Vrn-A1a in 10 lines and Vrn-A1c in one line. The dominant alleles of Vrn-B1a and Vrn-D1a were identified in 19 and 8 lines, respectively. The most common photoperiod-insensitive allele of Ppd-D1a was identified in 19 lines and three and four copy photoperiod-insensitive alleles (Ppd-B1a and Ppd-B1c) were present in five and one lines, respectively. All the lines were photoperiod-sensitive for the Ppd-A1 locus. All lines were semi-dwarf, having either of the two dwarfing alleles; 14 lines had the Rht-B1b (Rht-1) and the remaining had the Rht-D1b (Rht-2) dwarfing allele. The presence of the photoperiod-insensitive allele Ppd-D1a along with one or two spring alleles at the Vrn1 loci resulted in an earlier heading and better yield. Dwarfing genes were found to modify the heading time—the Rht-D1b allele advanced heading by three days and also showed superior effects on yield-contributing traits, indicating its beneficial role in yield under rain-fed conditions along with an appropriate combination of photoperiod and vernalization alleles. This study also identified the adaptability value of these allelic combinations for higher grain yield and protein content across the different the water-limited environments.